An Empirical Analysis of Competition in Print Adversiting among Paid and Free Newspapers - Geoffrey Brooke; Lydia Cheung (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
This paper examines the competition in the print newspaper advertising market in New Zealand, which involves paid daily and free weekly titles. This is the first study to explore how different ownership structures across two newspaper segments affect the competitive forces in local geographic markets. We do so by constructing an original dataset of advertising rates. This has particular relevance in light of the Commerce Commission's recent rejection of the proposed NZME-Fairfax merger, and Fairfax's subsequent closure of 15 newspaper titles. We find strong evidence for competition between overlapping free weekly suburban titles. It is associated with a 11% decrease in the full tabloid page display advertising rate. We also find evidence of joint profit maximization between co-owned free weeklies and paid dailies. Our results support the Commission's decision and give crucial implication on market definition: small and large display ads in free weekly titles constitute two separate markets with dif erent clients. The large display ad market also includes advertising in paid daily titles. This market is competitive and will likely suffer if the merger were granted.
Keywords: D12; L11; L13; L41; 330; Newspaper; Print; Advertising; Ownership structure; Competition; Merger